Third generation sequencing transforms the way of the screening and diagnosis of thalassemia: a mini-review - Zhan, Lixia; Gui, Chunrong; Wei, Wei; Liu, Juliang; Gui, Baoheng (Frontiers in Pediatrics, 2023)
Thalassemia is an inherited blood disorder imposing a significant social and economic burden. Comprehensive screening strategies are essential for the prevention and management of this disease. Third-generation sequencing (TGS), a breakthrough technology, has shown great potential for screening and diagnostic applications in various diseases, while its application in thalassemia detection is still in its infancy. This review aims to understand the latest and most widespread uses, advantages of TGS technologies, as well as the challenges and solutions associated with their incorporation into routine screening and diagnosis of thalassemia. Overall, TGS has exhibited higher rates of positive detection and diagnostic accuracy compared to conventional methods and nextgeneration sequencing technologies, indicating that TGS will be a feasible option for clinical laboratories conducting in-house thalassemia testing. The implementation of TGS technology in thalassemia diagnosis will facilitate the development of effective prevention and management strategies, thereby reducing the burden of this disease on individuals and society.